Siklus Penjualan dan Peluang Bisnis Ikan Hias di Kecamatan Kalidoni Kota Palembang - Az Zahra, Shafira; Maya Sari, Adita; Maharani, Bela; Nurilah, Deavita; Aprilia, Marsela; Putri, Reka; Kusumawardhani, Widyaningtyas (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Zahra SA, Sari AM, Maharani B, Nurilah D, Aprilia M, Putri R, Kusumawardhani W. 2022. Sales cycle and business opportunities of ornamental fish in Kalidoni District Palembang City. In:Herlinda S et al, (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 786-792. Palembang: Penerbit & Percetakan Universitas Sriwijaya(UNSRI).Ornamental fish are used as one of the mainstays to beautify homes with very beautiful motifs, this can open up business opportunities and the sales cycle for ornamental fish. The purpose of this survey is to find out how the turnover or cycle of ornamental fish sales is and to find out how big the business opportunity for selling ornamental fish is in Kalidoni District, Palembang City. The method used in this survey is to directly interview ornamental fish business owners with data analyzed using SWOT analysis. The results showed that about 78% of the incoming fish supply came from outside the city. Shipping from outside the city greatly affects the existing supply of ornamental fish. Delivery of ornamental fish out of town ranged between 100-200 tails. The selling price of fish varies from the cheapest price of Rp. 2,000 and the most expensive price of around Rp. 200,000 to 300,000 per head. This ornamental fish business has a very large profit depending on the diversity of fish and the selling price. So, the ornamental fish business in Kalidoni District, Palembang city is profitable.